ANALYSIS OF FACTORS DETERMINING PRODUCTION AND INCOME OF DRYLAND MAIZE FARMERS IN THE BORDER AREA OF KOBALIMA TIMUR DISTRICT MALAKA REGENCY - Un, Paulus; Adar, Damianus; Darlen, Maria Fransiska; Mahendra, Bayu (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
A This research was conducted in Kobalima Timur sub-district, namely in Alas Utara village and Kota Biru village. The objectives of this study were: 1) To identify factors that influence the level of production and income of corn farming businesses of dry land farmers in border areas; 2) To find out the amount of production and income obtained by corn farmers in dry land border areas.The selection of research locations was carried out by simple random sampling, namely selecting 2 villages out of 5 villages that directly border with Timor Leste, namely Alas Utara village and Kota Biru village. The selection of sample farmers was carried out using the simple random sampling method of 20% of the corn farmer population in the 2 selected villages, namely 32 corn farmers in Alas Utara village and 34 corn farmers in Kota Biru village. so that 66 farmers were obtained as respondents.The results of the study showed that: 1) Factors that significantly influenced the level of corn farming production in the border area of Kobalima Timur Sub-district, Malaka Regency were land area, selling price, and labor. Meanwhile, farming experience, number of seeds and education level do not significantly affect corn production; 2) The income of corn farmers in the border area of East Kobalima sub-district is IDR 15,823,252 per hectare